2021
DOI: 10.1038/s41598-020-80533-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural aspects of lesional and non-lesional skin microbiota reveal key community changes in leprosy patients from India

Abstract: Although skin is the primary affected organ in Leprosy, the role of the skin microbiome in its pathogenesis is not well understood. Recent reports have shown that skin of leprosy patients (LP) harbours perturbed microbiota which grants inflammation and disease progression. Herein, we present the results of nested Polymerase Chain Reaction-Denaturing Gradient Gel Electrophoresis (PCR-DGGE) which was initially performed for investigating the diversity of bacterial communities from lesional skin (LS) and non-lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The core’s microbiome present in at least 50% of Mtb infected individuals was represented only by Paracoccus, a gram-negative non-motile which genus, previously associated with infections, including leprosy and other skin infections where the skin microbiota had a relatively higher abundance of the bacteria compared to healthy controls 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The core’s microbiome present in at least 50% of Mtb infected individuals was represented only by Paracoccus, a gram-negative non-motile which genus, previously associated with infections, including leprosy and other skin infections where the skin microbiota had a relatively higher abundance of the bacteria compared to healthy controls 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal blood flow changed the hydration levels of skin that impacted the resident microbial community structure. 24 Figure 3: Models of dysbiosis of skin-resident microbes. 23 Growing evidence identified the lower diversity in the leprosy patient's skin microbiome than in the healthy subjects; assumed to be associated with the disease severity, colonization of pathogens, and the use of MDT.…”
Section: Skin Microbiome Dysbiosis In Leprosy Patientsmentioning
confidence: 99%
“…Reduction in the diversity of skin microbiota was observed in freshly diagnosis leprosy patients, those at various stages of MDT, and post MDT; these indicated that both the interaction between M. leprae-skin microbial community and the ongoing therapeutic regimen impacted the skin microbial variation. [24][25][26] Silva et al, studied how microbiota of leprous lesions had different bacterial skin composition than healthy subjects using Sanger and massively parallel small subunit rRNA (SSU) rRNA gene sequencing. Four main phyla were observed in the taxonomic analysis of leprous skin lesions: Proteobacteria, Firmicutes, Bacteroidetes, and Actinobacteria.…”
Section: Skin Microbiome Dysbiosis In Leprosy Patientsmentioning
confidence: 99%
See 1 more Smart Citation